Ficus hispida Linn.: A review of its pharmacognostic and ethnomedicinal properties - Ali, Mohammad; Chaudhary, Nisha (Pharmacognosy Reviews)
Ficus hispida (FH) Linn. is a moderate sized tree found throughout the year and is grown wild or cultivated for its edible fruits and folklore value. Traditionally, different parts of the plant have been used in the treatment of ulcers, psoriasis, anemia, piles jaundice, vitiligo, hemorrhage, diabetes, convulsion, hepatitis, dysentery, biliousness, and as lactagogue and purgative. FH contains wide varieties of bioactives from different phytochemical groups like alkaloids, carbohydrates, proteins and amino acids, sterols, phenols, flavonoids, gums and mucilage, glycosides, saponins, and terpenes. Various scientific works have been published to establish the scientific basis of traditional medicinal values attributed to FH. Furthermore, newer pharmacological activities like antineoplastic, cardioprotective, neuroprotective and anti-inflammatory effects were also reported recently. Till now, no work has been published to elaborate the pharmacognostic features of FH Linn. The present review is, therefore, an effort to give a detailed account on its pharmacognosy and phytochemistry, and an extensive survey on its pharmacological activities. Moreover, we are trying to establish the mechanism of action behind its earlier reported pharmacology. The review also looks at the future formulation based delivery approaches of its lipophilic bioactives, which is done to enhance its dissolution so as to increase its bioavailability, and thus the associated pharmacological action.
Keywords: Bioavailability; ethnomedicinal properties; extraction method; Ficus hispida; pharmacognosy